Hex Hall - Hawkins, Rachel, 1979- (Disney/Hyperion Books, 2010)
When Sophie attracts too much human attention for a prom-night spell gone horribly wrong, she is exiled to Hex Hall, an isolated reform school for wayward Prodigium, a.k.a. witches, faeries, and shapeshifters.